PENGARUH MODERNISASI SISTEM ADMINISTRASI PAJAK DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK YANG BERPROFESI SEBAGAI DOSEN DI PERGURUAN TINGGI SWASTA (Studi Kasus Dosen Universitas Trisakti) - Tyas Pambudi (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2016)
The purpose of this study was to determine the effect of tax administration system modernization and taxation knowledge on taxpayers who work as lecturers in private universities. The data used are primary data by distributing questionnaires to lecturer paxpayers in private universities. The population that will be the object of research is all lecturer taxpayers at Trisakti University. The sampling technique used was accidental sampling. This study uses a method of linear regression analysis. The results show that the modernization of the tax administration system and taxation knowledge has a positive and significant effect on taxpayer compliance as a lecturer in private universities.